2007
DOI: 10.1089/cpb.2007.9993
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Virtual Reality Pain Attenuation

Abstract: During the past decade, virtual reality (VR) has gained recognition as a means of attenuating pain during medical procedures. However, while investigators have examined the effects of virtual environments on level of distraction, subjective pain intensity, and brain activity, there have been only a handful of investigations into the neurobiological mechanisms associated with VR's efficacy. In an effort to explain how VR may alter pain perception and produce analgesia, as well as to guide the development of nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
137
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(153 citation statements)
references
References 52 publications
3
137
0
3
Order By: Relevance
“…These numerous studies have demonstrated that VR is an effective tool in significantly reducing pain a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 in acute pain situations. The "gate theory" of attention is the most widely accepted model in explaining the impact of VR on pain [16,17]. Gate theory of attention postulates that VR reduces the perception of pain by absorbing and diverting attention away from the pain.…”
Section: Introductionmentioning
confidence: 99%
“…These numerous studies have demonstrated that VR is an effective tool in significantly reducing pain a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 in acute pain situations. The "gate theory" of attention is the most widely accepted model in explaining the impact of VR on pain [16,17]. Gate theory of attention postulates that VR reduces the perception of pain by absorbing and diverting attention away from the pain.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality analgesia has been speculated to be the result of distraction. Recently, advancement in neuro-imaging studies has revealed how VR distraction modulates pain processing in brain regions known as the pain matrix [11] [12]. Neuroimaging studies have identified several brain regions that are consistently activated during nociceptive stimulation.…”
Section: Virtual Reality and Pain Managementmentioning
confidence: 99%
“…(Gold et al, 2007;Botella et al, 2008). Active engagement in VR activity, and the medium's immersive nature, involves the patient's attention more intensively (compared with other methods) -and thus can be a significantly more effective tool in pain alleviation.…”
Section: Introductionmentioning
confidence: 99%